Activating IL-6/STAT3 Enhances Protein Stability of Proteasome 20S α+β in Colorectal Cancer by miR-1254. (14th May 2022) - Ren, Weiguo; Zhang, Xuexiu; Li, Qiang; Pu, Chibin; Zhang, Decai
Abstract : A widely recognized feature of colorectal cancer (CRC) is an increase in cytokine levels, which result in an inflammatory environment in the tumor. Interleukin-6 (IL-6) is a robust protumor cytokine. Several studies suggest that IL-6 plays a role in the development of tumors. Most intracellular protein breakdown occurs in eukaryotes via the ubiquitin-proteasome pathway; this mechanism may also be involved in cancer pathogenesis. The tumor tissues and paracancerous tissues were collected from 90 patients with colorectal cancer. The expressions of pSTAT3, proteasome 20S α + β, miR-1254, and PSMD1 in tissues were detected by immunohistochemistry, ELISA, and qRT-PCR, and the effects of pSTAT3 and proteasome 20s α + β expressions on the survival of patients were studied. HCT116 and HCT116-R cells were cultured and added IL-6, AG490, STAT3 plasmid, or overexpression/knockdown of miR-1254 in cells. Immunofluorescence, western blot, qRT-PCR, double luciferase gene reporter assay, and flow cytometry were used to detect the expression of pSTAT3, STAT3, proteasome 20s α + β, miR-1254, and PSMD1 and cell cycle. The nude mouse xenograft model was constructed and divided into 3 groups: PBS group, IL-6 treatment group, and IL-6+miR-1254 mimic group. After 28 days, the tumor tissues were collected, and the expressions of miR-1254, pSTST3, proteasome 20s α + β, and PSMD1 in the tissues were detected by qRT-PCR and immunohistochemistry, respectively. Our study discovered that the level of proteasome 20S α + β had a strong connection with pSTAT3 in CRC patients. They were also linked to the development and clinical outcome of CRC. In addition, we found that IL-6 dramatically increased the expression of proteasome 20S α + β and pSTAT3; however, it did not affect the proteasome 20S α + β mRNA synthesis. Circulating proteasome concentration correlated with tumor tissue proteasome 20S α + β . STAT3 could occupy the miR-1254 promoter to inhibit transcription, and it could suppressed miR-1254 which targeted PSMD10, promoting proteasome 20S α + β protein stability. This is a prospective target for developing a new colorectal cancer therapy strategy.